Pengembangan Program Pencegahan dan Pengendalian Infeksi COVID-19 dalam Mempertahankan Status Kesehatan pada Tenaga Kesehatan di Rumah Sakit Kota Medan - Hasibuan, Muhammad Taufik Daniel; Silaen, Harsudianto (Jurnal Riset Hesti Medan, 2021)
The COVID-19 infection prevention and control program in hospitals is an effort to provide guidance for health workers to stay healthy, safe, productive, and the community gets services that meet standards. Health workers who work in hospitals are very vulnerable to being exposed to Â COVID -19, so it is very important that health workers and policy makers understand the basic concepts of infectious diseases. The purpose of this study was to develop a program to prevent and control covid-19 infection in maintaining the health status of health workers at the Medan City Hospital. The type of research used is action research. The participants in this study were 14 people consisting of 2 parts, namely 1) Participants for qualitative data were taken from managerial such as medical services, nursing, medical records, infection prevention and control units, and the head of the room. 2) Participants for quantitative data are taken from health workers, namely nurses. Data collection in this study used various methods, namely individual interviews, observation, self-report, focus group discussions and several data collection tools, namely interview guides, focus group discussion guides, questionnaires, observation sheets, and supporting tools, namely voice recorders. The results of this study obtained outputs, namely standard operating procedures for the prevention and control of covid-19 infection, and from the results of health status checks on health workers from before and after the implementation of the Â COVID -19 infection prevention and control program, the results were before (PCR/Antigen: Negative). 71.43%, Positive: 28.57%; Vital sign normal: 85.71%, Abnormal 14.29%), and after (PCR/Antigen: Negative 85.71%, Positive: 14.29%; Vital sign normal: 100%). This proves that there is an influence of the Covid-19 infection prevention and control program in maintaining the health status of health workers in hospitals. Suggestions to hospital leaders to continue to evaluate prevention and control programs for COVID-19 infection in accordance with developments and the situation at hand.